Trends in pediatric ocular trauma by year from 2007 to 2014 - Uppuluri, Siri; Uppuluri, Aditya; Zarbin, Marco A.; Bhagat, Neelakshi (Digital Journal of Ophthalmology, 2024)
Introduction The objective of this retrospective, cross-sectional study was to describe trends by year in demographics, hospital course, and types of ocular and nonocular traumatic injuries in the pediatric population (ages 0-17 years) between 2007 to 2014, as reported by the National Trauma Data Bank (NTDB). Methods Trends in the epidemiology, hospital course, and types of ocular and nonocular injuries by year occurring in children ages 0-17 years between the years 2007 to 2014 were described using data acquired from the NTDB. The NTDB reports data from participating institutions in the United States on emergency department (ED) visits resulting in admission, mortality, or transfer to another hospital. Descriptive statistical analysis was performed using IBM SPSS 23. Results In total, 44,937 cases were identified in the cohort. Across all years, by gender the majority of cases occurred in males, and by race, the majority of cases occurred in Whites. By age group, each year the plurality of cases occurred in the adolescents (ages 13-17 years) subgroup. Mortality rate ranged from 0% (no deaths reported) in 2014 to 3.6% in 2011. Types of ocular injury most commonly observed cumulatively in the 8-year period included ocular adnexal contusion (n = 14,355), open wound adnexa (13,145), and orbital floor fracture (11,891). The top three causes of injury across all years were motor vehicle accidents, accidental falls, and being hit by foreign body/object/person (nonassault). Conclusions Overall, nearly 45,000 cases of ocular injury in children ages 0 to 17 presented to EDs between 2007 to 2014. By age, race, and gender, each year the majority of cases occurred in adolescents (ages 13-17 years), Whites, and males. The most commonly occurring ocular injury was ocular adnexal contusion in all years except 2013, when open wound adnexal injury was the most common.